Robots, Artificial Intelligence, and Service Automation in Travel, Tourism and Hospitality - Ivanov, Stanislav; Webster, Craig (Emerald Publishing Limited, 2019)
Using a combination of theoretical discussion and real-world case studies, this book focuses on current and future use of RAISA technologies in the tourism economy, including examples from the hotel, restaurant, travel agency, museum, and events industries.